Modelling the impact of ecosystem fragmentation on ecosystem services in the degraded Ethiopian highlands - Tegegne Molla Sitotaw; Louise Willemen; Derege Tsegaye Meshesha; Martha Weldemichael; Andrew Nelson (Ecological Informatics)
Humans shape landscapes to optimise food, fibre, and fuel production. These modifications often fragment ecosystems and degrade ecological functions over time, particularly regulating and cultural ecosystem services (ES). Understanding how ecosystem fragmentation influences the temporal dynamics of ES is critical for biodiversity conservation and sustainable management under global environmental and climate change. Despite its importance, the role of fragmentation patterns in shaping ES over time remains underexplored. This study addresses this gap by assessing how fragmentation metrics—ecosystem area, perimeter-area ratio, and patch proximity—impact four key ES (wetland grass biomass, microclimate heat stress regulation, crop pollination, and nature-based tourism) in the degraded Ethiopian highlands. Using spatial generalized additive models (GAMs), we combined fragmentation metrics with relevant biophysical variables to model ES patterns for 2020 and extrapolated back to 2000 with year-specific remote sensing-based predictors. Our results reveal substantial temporal declines in all four ES driven by both linear and non-linear effects of ecosystem fragmentation. Over two decades, reductions in ecosystem area (25 %), increases in the perimeter-area ratio (15 %), and declines in patch proximity (30 %) were strongly associated with significant losses in all four ES. Ecosystem fragmentation not only reduces ES supply but also alters their spatial and temporal distribution. Therefore, incorporating fragmentation dynamics into ES modelling is crucial for accurate and comprehensive assessments of ES distribution. By demonstrating a novel temporal perspective on the relationship between landscape configuration and ES, our findings provide robust, data-driven insights for landscape planning and the development of sustainable conservation strategies in fragmented landscapes.